On gw-Prime Submodules - Said, Hazhar Ali; Jabbar, Adil Kadir (Iraqi Journal of Science, 2023)
Our aim in this work is to investigate prime submodules and prove some properties of them. We study the relations between prime submodules of a given module and the extension of prime submodules. The relations between prime submodules of two given modules and the prime submodules in the direct product of their quotient module are studied and investigated.